Harmonization and Tax Stimulation of Innovative Activity of Kazakhstan in the EEU - LUKPANOVA, Zhanar; KUDAYBERGENOVA, Saltanat; ULAKOV, Nazar; SEMBEKOV, Amir; IGLIKOVA, Dinara; MUKASHEVA, Kuralay (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
In Kazakhstan, as in most countries of the world, the tax system is viewed not only as a tool to ensure the formation of the revenue side of the budget, but also as a mechanism for macroeconomic regulation that allows stimulating the development of the economy in a given direction. At present, the domestic economy has reached a critical phase of its development: there is a need to replace the raw-material development scenario with an innovative model. As a result of the research, the analysis of forms and methods of stimulating innovation activity was made with an emphasis on financial and tax incentive tools, the possibility of introducing a new special taxation regime and certain tax incentives for innovation entities was determined, an analysis of the development of SEZ in the Republic of Kazakhstan was made and a model for forecasting the indicators of innovation development of the region And tax revenues from the subjects of innovation.